Right-to-know - Black, Matthew L.; MARCOM Group, Ltd. (Boothwyn, Pa.) (Boothwyn, Pa. : The MARCOM Group, Ltd., 1997)
Discusses the effects of hazardous chemicals on the body, how to deal with these substances in the workplace, and how to seek'Right-to-know' information and appropriate documentation surrrounding the use of these substances
Building and construction companies -- Cleaning and maintenance operations -- Industrial facilities
Title from container
Presenter's guide includes an introduction to the program, preparing for the presentation, conducting the session, an outline of major points in the program, and accompanying materials
Editors, D. Preston Lee III, C.W. Gallagher Jr
Keywords: Hazardous substances -- Safety measures; Hazardous substances -- Health aspects; Chemicals -- Safety measures; Hazardous substances; Industrial safety